The politics of seduction - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
CTA s Annual Report 2002 is a fine example of the liven it up strategy being followed by those organisations which are not, as many are these days, cutting their annual report down to a financial statement.